Experimental Study on Dust Removal Performance of Electrostatic Water Film Cyclone Dust Collector - Di Zhang; Zuyun Chen; Fangquan Zhong; Ziyi Zhou (International Journal of Rotating Machinery, 2023)
Due to their limitations, conventional electric and water film dust removal methods struggle to handle fine dust. This study presented information on and examined the electrostatic water film cyclone dust collector (EWFCDC). By using the variable control approach, the impacts of inlet flow speed, water film flow rate, and corona pole form on dust removal performance were investigated. At EWFCDC, an orthogonal test was carried out to improve the test design and operating parameters based on the single-factor experiment. The pressure loss in the cyclone cylinder, when there is no water film and no corona pole, is a quadratic function of the inlet flow speed, and it is 2418.10 Pa at a 21.25 m/s inlet flow speed. The effectiveness of dust removal may be increased by increasing the water film flow rate. The effectiveness of dust removal is greatly influenced by the type of corona pole used, and cage needling thread is the optimal type. The electrostatic water film cyclone’s multimechanism coupling significantly increases the effectiveness of dust removal.